ANALISIS BIAYA RELEVAN UNTUK PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA PT. BS POLYMER - Husnawati A. Rahman (Jurnal Bisnis dan Kewirausahaan, 2016)
This study aimed to determine whether special orders can be accepted or not by using the analysis of the relevant costs. The method of analysis is relevant costs and not relevan.Analisis separation of semi-variable costs into fixed costs and variable costs, by using the method of least squares regression (least square regression method) Analysis of relevant cost alternative choice by special order and without special orders , where the variable used is the Contribution Margin. While the results showed that PT.BS Polymer has not done a cost analysis relevant tepat.Dari results of analysis of the relevant costs, in particular the decision to accept or reject special orders showed that of the proposed alternative can provide benefits for special order perusahaan.Berdasarkan results of the analysis show that the special order of PT.Semen Tonasa and PT Semen Batam acceptable.